EDUKASI MANFAAT PELATIHAN YOGA DAN PELATIHAN KOORDINASI NEUROMUSKULAR UNTUK MENCEGAH PENYAKIT MUSKULOSKELETAL SERTA PELAYANAN KESEHATAN PADA PEGAWAI DAN PEDAGANG PASAR - Wahyuni, N.; Andayani, N.L.N. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i03.p10, 2023)
The high incidence of musculoskeletal diseases and the various negative impacts they cause requires an effective prevention method. Based on the results of interviews with the Head of the Nyanggelan Market in Panjer Village, most of the market employees and traders had experienced musculoskeletal complaints due to various risk factors for musculoskeletal disease and most of the market employees and traders knew not yet the benefits of yoga training and neuromuscular coordination training in preventing work-related musculoskeletal diseases. The purpose of implementing this community service is to increase public knowledge about the benefits of yoga training and neuromuscular coordination training in preventing workrelated musculoskeletal diseases. The specific target to be achieved from this activity is to improve the level of public knowledge regarding the benefits of yoga training and neuromuscular coordination training in preventing work-related musculoskeletal diseases. The method that will be used to achieve the goal is to carry out community service by coming directly to the Nyanggelan Market in Panjer Village to provide education about the benefits of yoga training and neuromuscular coordination training in preventing work-related musculoskeletal diseases. This service activity involved 5 members consisting of 3 doctors, and 2 students.The service will be carried out in one day, where before carrying out the activities the team conducts a survey and assessment at the Nyanggelan Market in Panjer Village. The form of activity that will be carried out in this service is to provide education about the benefits of yoga training and neuromuscular coordination training in preventing work-related musculoskeletal diseases. To facilitate participants' understanding, education was carried out by distributing brochures to market employees and traders. The service is carried out while continuing to implement the protocol to prevent the spread of COVID-19 infection. Keywords: yoga, neuromuscular coordination, musculoskeletal.